47 Targeted therapy using intradermal injection of etanercept for remission induction in discoid lupus erythematosus (TARGET-DLE): results from a proof-of-concept phase II trial. (April 2019) - Md Yusof, Md Yuzaiful; Wittmann, Miriam; Fernandez, Catherine; Wilson, Duncan; Edward, Sara; Abignano, Giuseppina; Alase, Adewonuola; Laws, Philip; Goodfield, Mark; Emery, Paul; Vital, Edward
Abstract : Background: A significant proportion of patients with discoid lupus erythematosus (DLE) are resistant to conventional therapies. Tumour necrosis factor (TNF) is pathogenic in DLE. A concern with systemic TNF-i administration is induction of pathogenic autoantibodies and flare of disease. This could be overcome using a low-dose intra-dermal injection, which may be sufficient to neutralise the TNF in lesions, without systemic TNF effects. The objective of this trial was to assess the efficacy and safety of a novel route of administration of a TNF-i using a low dose intra-dermal injection of etanercept (ETN) for remission induction in DLE. Methods: A prospective single arm, Simons 2-stage minimax design with Hybrid adaptation, phase II open label trial was conducted in Leeds [NCT02656082 ]. Key inclusion criteria were i) adults aged 1880 y; ii)oneactive DLE lesion and iii) refractory to anti-malarials. One index lesion with the highest activity was treated with weekly intra-dermal injection of up to 10 mg ETN. The primary endpoint was 6 patients achieving the modified limited Score of Activity and Damage in DLE (ML-SADDLE) 20 response (defined as reduction 20% in total activity comprises erythema, induration and scaling from baseline) at Week 12 for a Phase 3 trial to be recommended. Secondary endpoints included change in objective outcome measures; lesional thermography and laser Doppler imaging. Results: All 25 DLE patients were recruited over 18 months (18 female, mean age 47±12 y, 6 had SLE, 9 had positive ANA and median (range) no. of previous systemic therapies was 5 (116) 17 patients completed the primary efficacy assessment [Did not attend Week 12 visit=1, early withdrawals=7 (personal choice=2, AE=2, worsening of DLE=1, non-compliance=1, pregnant=1)]. The primary endpoint was met with 13/25 (52%, 95% CI 3173) meeting the ML-SADDLE 20 in full-set analysis. The rates for ML-SADDLE 50 and 70 were 48% and 20% respectively. Key secondary endpoints were met (table 1 ). Fifty-one AEs (treatment-emergent=28, Grade 3/4=4) were recorded. There was no worsening of BILAG or SLEDAI in patients with SLE. Trough serum ETN levels were detected in 6/23 (26%). Conclusions: Intradermal injection of ETN substantially reduced clinical activity, met its primary, secondary endpoints and was tolerable in DLE patients who were refractory to anti-malarials and other systemic therapies. This drug warrants further development in multi-centre trials. Analyses of other imaging and histological biomarkers are ongoing and can help stratifying patients for response. Funding Source(s): National Institute of Health Research